Morphological Awareness: Students’ Proficiency in Analyzing Derivational Affixes in English - Efrika Siboro; Barli Bram (Universitas PGRI Madiun, 2020)
This paper examined students’ proficiency in analyzing derivational affixes in English. The objective of this research was to discover how far the students’ capability in analyzing errors of prefixes and suffixes in English sentences. The researchers limited this study to focus only on derivational affixes. In order to obtain the data, students were tested. The participants of this research were undergraduate students of the English education department at STKIP Pamane Talino, West Kalimantan. The researchers used a descriptive qualitative method to analyze the data. The results showed the average of students’ proficiency in analyzing prefixes and suffixes in sentences was 68.57%. More specifically, seven students (33.33%) belonged to the “excellent” category, seven students (33.33%) belonged to the “very good” category, four students (19.04%) were categorized as a “good” category, two students (9.52%) were classified as a “fair” category, and one student (4.76%) belonged to the “poor” category.